Examining Anti-Corruption Discourse: Discursive Resistance of Generation Z in Nepal on X - Vindy Thahura Ramadhani; Setiono Sugiharto (STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
This study investigates anti-corruption discourse generated by Generation Z members in social media comments on platform X in reaction to anti-corruption protest announcements in Nepal. Whereas prior work on digital political engagement has tended to take a more macro-centric view of mobilization and organizational participation, there has been less focus on how mundane resistance is expressed in daily online exchanges. Drawing on Critical Discourse Analysis (CDA) and a qualitative netnographic approach, the study analyzes public digital comments to examine the linguistic construction of anti-corruption demands at the micro level. The analysis shows that Generation Z uses a variety of discursive techniques such as supportive alignment, imperative expressions, moral condemnation, generational positioning, and affective intensification to articulate resistance. These strategies function as low-risk symbolic forms of everyday resistance that challenge political legitimacy and communicate collective dissatisfaction without formal organization. The findings indicate that social media comments operate as a major locus of digital political participation where anti-corruption criticism is normalized, circulated, and sustained through interactive communication practices. The study advances studies on critical discourse analysis by expanding the concept of everyday (or grassroots) resistance into digitally mediated environments and emphasizing the political implications of comment-level expression in contemporary networked publics.